31.8k views
3 votes
13–86 A radiation shield that has the same emissivity e3 on both sides is placed between two large parallel plates, which are maintained at uniform temperatures of T1 5 650 K and T2 5 400 K and have emissivities of e1 5 0.6 and e2 5 0.9, respectively. Determine the emissivity of the radiation shield if the radiation heat transfer between the plates is to be reduced to 15 percent of that without the radiation shield.

User Atonyc
by
5.4k points

1 Answer

4 votes

Answer:

The emissivity of the radiation shield is
e_3 = 0.580

Step-by-step explanation:

From the question we are told that

The temperature of the first parallel plate is
T_1 = 650K

The temperature of the second parallel plate is
T_2 = 400K

The emissivity of first plate is
e_1 = 0.6

The emissivity of first plate is
e_2 = 0.9

Generally the total radiation heat that is been transferred without the shield is mathematically represented as


Q_1 = (\sigma (T_1 ^4 - T_2 ^4))/((1)/(e1 ) + (1)/(e_2) -1 )

Where
\sigma is the Stefan-Boltzmann constant which has a value
5.67 *10^(-8) \ W \cdot m^(-2) \cdot K^(-1)

Substituting values


Q_1 = ( 5.67 *10^(-8) (650 ^4 - 400 ^4))/((1)/(0.6 ) + (1)/(0.9) -1 )


Q_1 = 4876.8 \ W/m^2

From the question we are told the that using the radiation shield would reduce the radiation heat transfer by 15%

So the new heat transfer is


Q_2 = (15)/(100) * Q_1

So
Q_2 = (15)/(100) * 4876.8


Q_2 = 731.52 W/m^2

Now this new radiation heat transfer can be mathematically represented as


Q_2 = (\sigma (T_1 ^4 - T_2 ^4))/( [(1)/(e_1 ) + (1)/(e_2 ) - 1 ] + n [(1)/(e_3) + (1)/(e_3) -1 ])

Where
e_3 the emissivity of the radiation shield and n is the number of radiation shield

Substituting values


731.52 = (5.67 *10^(-8) (650 ^4 - 400 ^4))/( [(1)/(0.6) + (1)/(0.9 ) - 1 ] + 1 [(1)/(e_3) + (1)/(e_3) -1 ])


731.52 = (1.4175*10^(-5))/( [(1)/(0.6) + (1)/(0.9 ) - 1 ] + 1 [(1)/(e_3) + (1)/(e_3) -1 ])


[(1)/(0.6) + (1)/(0.9 ) - 1 ] + 1 [(1)/(e_3) + (1)/(e_3) -1 ] = (1.4175*10^(-5))/(731.52)


[(1)/(0.6) + (1)/(0.9 ) - 1 ] + 1 [(1)/(e_3) + (1)/(e_3) -1 ] = 1.9377*10^(-8)


1 [(1)/(e_3) + (1)/(e_3) -1 ] = 1.9377*10^(-8) - [(1)/(0.6) + (1)/(0.9 ) - 1 ]


(1)/(e_3) + (1)/(e_3) = 1 .7222222416


e_3 = 0.580

User Merry
by
5.6k points